Are consumers sensitive to large retailers' sustainable practices? A semiotic analysis in the French context. (September 2016) - Kessous, Aurélie; Boncori, Anne-Laure; Paché, Gilles
Abstract: This paper seeks to discover consumer perceptions related to the adoption of sustainable transport practices by the French large retail industry. Using 20 semi-structured interviews and the semiotic square method, this research sheds light on a set of structured postures of consumers' perceptions according to a semantic axis: conjunction vs. disjunction. The recourse to a socio-semiotic reading here favours a deeper comprehension of the question of consumers' trust in large retailers. It proposes a typology of four distinct virtual strategies responding to the diverse consumer perceptions brought to light: persuasion, rejection, suspicion, and alignment. This leads to a discussion of the strategies offered by different large retailers to meet their consumers' perceptions and expectations. Lastly, the results outline the importance of deploying targeted communication and of aligning sustainable transport practices in accordance with the identified consumer postures.